Dismantling public policy preferences, strategies, and effects - Bauer, Michael W. (Oxford : Oxford University Press, 2013)
'Dismantling Public Policy' seeks to develop a comparative approach to understanding policy dismantling. It looks at the cutting, reduction, diminution or complete removal of existing policies.
Description based on online resource; title from home page (viewed on Dec. 20, 2012).
Includes bibliographical references and index.
Keywords: Political planning